Assessment of sensory and nutritional attributes of foxtail millet-based food products - Arora, Laghima; Aggarwal, Renuka; Dhaliwal, Inderpreet; Gupta, Om Prakash; Kaushik, Prashant (Frontiers in Nutrition, 2023)
Millets are a rich source of many health-promoting nutrients as well as bioactive compounds such as dietary fibers, antioxidants, macro and micronutrients etc. compared to other staple cereals such as rice, wheat and maize. These nutrients play a central role in the world nutritional security. Despite the inbuilt nutritional benefits, the production of millets has witnessed sharp decline owing to taste preferences, keeping quality and challenges associated with food preparation from millets. To sensitize the consumers about the nutritional benefits of foxtail millet, the present study was planned to formulate and nutritionally evaluate eight diversified foxtail millet-based food products namely rusk, kheer, pinni, sattu, vegetable dalia, cookies, bar and papad by replacing commonly used cereals such as wheat and rice. The products prepared from Foxtail millet were found to have high acceptability with mean score of more than 8.00. These diversified food products showed higher protein content ranging from 10.98 to 16.10 g/ 100 g, with the highest protein found in Foxtail millet kheer (16.01 g / 100 g). The resistant starch content and predicted glycemic index (PGI) of these products ranged between 13.67 to 22.61 g/ 100 g and 46.12 to 57.55, respectively, with the highest resistant starch (22.61±0.69 g /100 g) and lowest PGI (48.42±0.20) found in millet bar. The high resistant starch and low PGI in foxtail millet products suggest that they could serve as an excellent food source suitable for diabetics. The obtained results suggest that all the Foxtail millet-based value-added products have superior nutrient profile and are highly acceptable than the traditional products. Inclusion of these foods in the diets of the population may help in the prevention of malnutrition and Type 2 diabetes.